Eksistensi Local Self-Government dan Tantangannya dalam Pembentukan Produk Hukum Desa yang Responsif - Ahmad Jaelani; Hermansyah; Utang Rosidin (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2026)
This study examines the existence of local self-government within the framework of village governance in Indonesia and its relationship to the formation of responsive village legal products. Employing normative legal research methods with statutory, conceptual, and historical approaches, the study analyses primary, secondary, and tertiary legal materials through qualitative-prescriptive analysis. The research yields two principal findings. First, although the existence of local self-government has received strong constitutional recognition through the principles of recognition and subsidiarity under Law Number 6 of 2014 on Villages and its amendments, the autonomy realised in practice remains largely formal rather than substantive; the tension between villages' normative authority and supra-village regulatory intervention, weak institutional capacity, and the ambiguous position of village regulations within the national legislative hierarchy constitute real structural obstacles. Second, the formation of responsive village legal products remains far from ideal: inadequate problem identification, ceremonial public participation, and the absence of systematic implementation evaluation mechanisms have caused most village regulations to exhibit the character of formalistic autonomous law rather than responsive law oriented toward social problem-solving. The study concludes that strengthening the existence of local self-government and the responsiveness of village legal products are two mutually determining agendas that must be pursued simultaneously through institutional capacity reform, substantive participation mechanisms, integration of local wisdom, and the repositioning of village regulations within the national legal system.